Antirust lubricant as well as preparation method and application thereof

By using graphene and other additives in anti-rust lubricants, a single-layer graphene film is formed, which solves the problem of corrosion and infection risks of medical stainless steel appliances, and achieves excellent anti-rust, oxidation and lubricating properties, extends medical devices lifespan and reduces the risk of infection.

CN119242369APending Publication Date: 2025-01-03CHANGSHA ZHANYING MEDICAL EQUIP CO LTD

Patent Information

Application Number
CN202411132701.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Medical stainless steel appliances are prone to corrosion during use, resulting in an increase in the risk of infection. The water-soluble substances in existing anti-rust lubricants contact the human body will increase the risk of infection. Moreover, strong acidic rust removers cause secondary rust on metals, affecting the life of the appliance. .

Method used

Develop an anti-rust lubricant containing graphene, dispersant, coagulation reducing agent, viscosity index improver, corrosion inhibitor, anti-rust additive and anti-oxidant additive. Graphene is prepared by microwave heating to form a single-layer graphene film to Anti-rust and lubrication, adopt low-cost methods suitable for industrial production.

Benefits of technology

The lubricant has excellent anti-rust, anti-oxidation, lubricating and antibacterial properties, which can extend the service life of medical devices, reduce the risk of infection, and show good performance in biocompatibility and chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242369A_ABST
    Figure CN119242369A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-rust lubricant as well as a preparation method and application thereof. The lubricant comprises the following components in parts by mass: 10-60 parts of base oil; 0.001 to 1 part of graphene; 0.1-3 parts of a dispersant; 0.1-3 parts of a pour point depressant; 0.1 to 1 part of a viscosity index improver; 0.1-3 parts of a corrosion inhibitor; 0.1-1 part of an antirust additive; 0.1 to 1 part of an antioxidant additive; and 27 to 89.4 parts of water. The lubricant has excellent anti-rust, anti-oxidation, lubricity and antibacterial properties. When being applied to medical instruments, the lubricating oil can effectively lubricate the surfaces and joint parts of the metal medical instruments, reduce the roughness of the joints of the instruments, improve the friction pair bearing capacity of the instruments, prevent the medical instruments from rusting too fast and prolong the service life of the medical instruments. The preparation method is simple, low in cost and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lubricant, in particular to an anti-rust lubricant, and also to a preparation method and application thereof, belonging to the technical field of material preparation and medical treatment. Background Art

[0002] Stainless steel instruments such as medical scalpels or other metal medical devices often come into contact with human tissue cells, blood or medical disinfectants, alcohol, sodium chloride and other solutions during daily use in hospitals, which will accelerate the corrosion of medical instruments and increase the risk of infection for patients. In order to extend the service life of medical stainless steel instruments, reduce the risk of infection for patients, and achieve the reuse of medical instruments, many hospitals use strong acid rust removers to remove rust from medical stainless steel instruments, and then perform anti-rust lubrication on the cleaned medical stainless steel instruments. However, strong acid rust removers also cause secondary corrosion to the metal while removing rust, and the water-soluble substances in the anti-rust lubricant are in direct contact with the human body, which will further increase the risk of infection for patients.

[0003] Therefore, the development of a new type of medical lubricant is of great significance to medical and health safety. Summary of the invention

[0004] In view of the problems existing in the prior art, the first object of the present invention is to provide a rust-proof lubricant having excellent rust-proof, anti-oxidation and lubricating properties, and also having excellent antibacterial properties.

[0005] The second object of the present invention is to provide a method for preparing a rust-proof lubricant, which is simple, low-cost and suitable for industrial production.

[0006] The third object of the present invention is to provide an application of an anti-rust lubricant. When used in medical devices, it can lubricate the contact surface of the device, reduce the roughness, and improve the bearing capacity of the friction pair of the device. At the same time, it forms an anti-rust film on the surface of the metal medical device to prevent the medical device from rusting too quickly and extend the service life of the medical device.

[0007] In order to achieve the above technical objectives, the present invention provides an anti-rust lubricant, which comprises the following components by weight:

[0008] 10-60 parts of base oil;

[0009] Graphene 0.001 to 1 part;

[0010] Dispersant 0.1-3 parts;

[0011] Pour point depressant 0.1 to 3 parts;

[0012] 0.1 to 1 part of viscosity index improver;

[0013] Corrosion inhibitor 0.1-3 parts;

[0014] 0.1 to 1 part of anti-rust additive;

[0015] Antioxidant additive 0.1-1 part;

[0016] 27-89.4 parts of water.

[0017] Graphene is added to the anti-rust lubricant of the present invention, and the anti-rust lubricant with added graphene can significantly improve the lubrication, anti-rust and load-bearing capacity of the coating device, and the graphene material is solidified into a film to isolate corrosive media such as oxygen and water molecules, thereby protecting the substrate. Secondly, the graphene prepared by microwave heating is conducive to the formation of a single-layer graphene in the base oil and maintaining the single-layer state for a long time, thereby stabilizing the performance of the lubricant, so that the lubricant has good biocompatibility and lubricity. In addition, the anti-rust lubricant of the present invention is easy to degrade, can be stored for a long time in a colorless and transparent state, and does not affect the use of the device.

[0018] As a preferred solution, the base oil includes poly-α-olefin base oil and / or mineral oil.

[0019] As a preferred solution, the base oil includes a poly-α-olefin base oil to which a surface modifier is added and / or a mineral oil to which a surface modifier is added.

[0020] As a preferred solution, the surface modifier includes stearic acid and / or oleic acid.

[0021] As a preferred solution, the graphene is prepared by heating a graphene precursor with microwaves. The graphene precursor includes at least one of graphite, graphite oxide, nanographene particles, graphene flakes, graphene composite materials, graphene derivative materials, and graphene oxide materials. Among them, the graphene derivative materials include fluorinated graphene. The graphene composite materials include α-Fe2O3 / graphene composite materials, CeO2 / graphene nanocomposites, etc.

[0022] As a preferred solution, when the graphene precursor is graphene oxide or fluorinated graphene, the base oil is a poly-α-olefin base oil; when the graphene precursor is an α-Fe2O3 / graphene composite material or a CeO2 / graphene nanocomposite material, the base oil is a mineral oil. For graphene prepared from different graphene precursors, selecting a more suitable base oil can further improve the stability of graphene in the base oil environment.

[0023] As a preferred solution, the dispersant includes at least one of isopropanol, cerium dioxide nanoparticles, α-Fe2O3 nanorods, modified long-chain alkanes with a carbon number of 10 to 30, stearic acid, oleic acid, and doped graphene.

[0024] Since graphene is a planar conjugated structure composed of sp2 hybridized carbon atoms, there are very strong π-π effects and van der Waals forces between its sheets, resulting in extremely poor dispersibility. Although traditional surfactants (such as SDBS, CTAB, Triton-X, Tween 80), polymer stabilizers (such as PVP, PSS, PDDA), etc. can all play a certain dispersing and stabilizing role on graphene, there are often problems such as large amount of dispersant and low graphene concentration, which affect the performance of the lubricant. Therefore, the dispersant used in the present invention is mostly to separate graphene on the physical level, which does not affect the overall performance of the lubricant, and when the present invention selects CeO2 / graphene nanocomposite as a graphene precursor, the storage time of the state of the single-layer graphene can be further extended.

[0025] As a preferred solution, the pour point depressant includes at least one of modified graphene, halogenated hydrocarbons, organic alcohols and poly-α-olefins, and the modified graphene contains at least one of a long-chain alkyl group with a carbon number of 10 to 50, a carboxyl group, a sulfonic acid group, an amino group and a fluoroalkyl group. The addition of the pour point depressant can effectively control the re-agglomeration of graphene, and complements the dispersant to effectively improve the stability of the single-layer graphene in the base oil.

[0026] As a preferred solution, the viscosity index improver includes at least one of hydrogenated styrene diene copolymer, polymethacrylate, ethylene propylene copolymer, and polyisobutylene. The viscosity index improver can be used to prepare multi-grade oils and improve viscosity-temperature performance. Adding a viscosity index improver to a lubricant can improve the viscosity index in a larger temperature range, improve lubricant performance, upgrade the grade of the lubricant, and extend the service life of the lubricant.

[0027] As a preferred solution, the corrosion inhibitor includes organic phosphonic acid and / or polycarboxylic acid.

[0028] As a preferred solution, the anti-rust additive includes at least one of octadecylamine oleate, cyclohexylamine stearate, and nitrogen heterocyclic compounds.

[0029] As a preferred solution, the antioxidant additive includes at least one of antimony dialkyl dithiocarbamate, zinc dialkyl dithiocarbamate, dialkyl dithiocarbamate, butylated hydroxytoluene, and tert-butylhydroquinone.

[0030] The present invention also provides a method for preparing an anti-rust lubricant, which comprises mixing graphene with base oil, adding a dispersant, a pour point depressant and a viscosity index improver, and then adding a corrosion inhibitor, an anti-rust additive, an antioxidant additive and water to obtain the anti-rust lubricant.

[0031] As a preferred solution, the graphene is mixed with the base oil and then preheated to 35-50°C.

[0032] As a preferred solution, the preparation process of the graphene is: dispersing the graphene precursor in an organic solvent and then heating it with a microwave to obtain the graphene. The microwave heating method can make the obtained graphene more dispersed, which is beneficial to improving the biocompatibility, lubricity, stability and degradability of the lubricant.

[0033] As a preferred solution, the organic solvent includes at least one of N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), tetrahydrofuran (THF), and chloroform.

[0034] As a preferred solution, the microwave heating conditions are: power of 600-800W, time of 1-30min.

[0035] As a preferred solution, when the organic solvent is N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP), the power of microwave heating is 800 W and the time is 1 to 10 min.

[0036] As a preferred solution, when the organic solvent is tetrahydrofuran (THF), the power of microwave heating is 600 W and the time is 8 to 20 min.

[0037] As a preferred solution, when the organic solvent is chloroform, the power of microwave heating is 600 W and the time is 10 to 30 min.

[0038] As a preferred solution, the whole process of preparing the rust-proof lubricant adopts microwave dispersion or ultrasonic dispersion. The whole process adopts microwave dispersion or ultrasonic dispersion to keep the graphene / graphene oxide in the lubricant in a single layer state, improve the biocompatibility and chemical stability of the lubricant, and ensure that the rust-proof lubricant can be preserved in a colorless and transparent state for a long time.

[0039] The present invention also provides an application of an anti-rust lubricant, which is used as an anti-rust lubricant for medical devices. The lubricant can significantly improve the anti-rust, anti-oxidation and antibacterial properties of medical devices, effectively lubricate the surface and joints of metal medical devices, reduce the roughness of the device connection, improve the bearing capacity of the friction pair of the device, improve the wear resistance of the device, and extend the service life of the medical device.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The lubricant of the present invention has excellent anti-rust, anti-oxidation and lubricating properties, and also has excellent antibacterial properties, biocompatibility and chemical stability;

[0042] (2) It can be applied to medical devices to lubricate the surface and joints of metal medical devices, reduce the roughness of the device connection, and improve the bearing capacity of the friction pair of the device. At the same time, it forms an anti-rust film on the surface of the metal medical device to prevent the medical device from rusting too quickly and extend the service life of the medical device;

[0043] (3) The lubricant preparation method is simple, low-cost, and suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The corrosion performance test diagram of the stainless steel sheet coated with the anti-rust lubricant of the present invention (left) and coated with a commercially available common lubricant product (right).

[0045] Figure 2 This is a corrosion performance test diagram of a stainless steel sheet coated with the lubricant prepared in Comparative Example 1 of the present invention.

[0046] Figure 3 This is a corrosion performance test diagram of a stainless steel sheet coated with the lubricant prepared in Comparative Example 2 of the present invention.

[0047] Figure 4 This is a corrosion performance test diagram of a stainless steel sheet coated with the lubricant prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0048] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Example 1

[0050] The following is a preparation process of a lubricant, as follows:

[0051] 1g of graphene oxide raw material was first immersed in 60ml of organic solvent dimethylformamide, fully stirred, and then heated at 800W for 10min to remove oxygen in graphene oxide. The obtained 0.12g of highly dispersed graphene was immediately added to the prepared 400ml (376.0g) poly-α-olefin base oil with added surface modifier (stearic acid), stirred evenly and put into a microwave graphene preparation furnace, set the microwave parameter to 200W, heated to 40°C, and then added 10ml of modified long-chain alkane dispersant (bromooctadecane, mass 10.2g), 10ml of Halogenated hydrocarbon pour point depressant (n-butyl bromide, mass 12.77g) and 10ml of ethylene propylene copolymer viscosity index improver (ethylene propylene copolymer T613, mass 8.7g) are dispersed by microwave for 10min to make the above materials blend into the base oil; then add 10ml of polycarboxylic acid corrosion inhibitor (11.5g), 10ml of oleic acid octadecylamine rust inhibitor (9.0g), 10ml of dialkyl dithiocarbamate antioxidation additive (10.1g), and microwave dispersion treatment at 800W for 60min, finally add 800ml of deionized water and stir evenly.

[0052] Example 2

[0053] The following is a preparation process of a lubricant, as follows:

[0054] 0.1g ZnO / graphene nanocomposite material is first immersed in 60ml organic solvent N-methylpyrrolidone, fully stirred, and then subjected to 800W microwave heating for 10min, added to the prepared 400ml mineral oil, stirred and then placed in a microwave graphene preparation furnace, set a 200W microwave parameter, heated to 40°C, and then 10g of α-Fe2O3 nanorod dispersant, 10g of modified graphene pour point depressant (platinum / graphene nanocomposite, 803693), and 10ml of polymethacrylate viscosity index improver are added in sequence, and microwave dispersion treatment is performed for 20min to allow the above materials to be integrated into the base oil; then 10ml of organic phosphonic acid corrosion inhibitor, 10ml of oleic acid octadecylamine rust inhibitor, and 10ml of dialkyl dithiocarbamate zinc antioxidant additive are added, and microwave dispersion treatment is performed at 800W for 80min, and finally 800ml of deionized water is added and stirred evenly.

[0055] Example 3

[0056] The following is a preparation process of a lubricant, as follows:

[0057] 0.13g ZnO / graphene nanocomposite material is first immersed in 60ml organic solvent N-methylpyrrolidone, fully stirred, and then subjected to 800W microwave heating for 10min, added to the prepared 400ml mineral oil, stirred and then placed in a microwave graphene preparation furnace, set a 200W microwave parameter, heated to 40°C, and then 10g of α-Fe2O3 nanorod dispersant, 10g of modified graphene pour point depressant (platinum / graphene nanocomposite, 803693), and 10ml of polymethacrylate viscosity index improver are added in sequence, and microwave dispersion treatment is performed for 20min to allow the above materials to be integrated into the base oil; then 10ml of organic phosphonic acid corrosion inhibitor, 10ml of oleic acid octadecylamine rust inhibitor, and 10ml of dialkyl dithiocarbamate zinc antioxidant additive are added, and microwave dispersion treatment is performed at 800W for 80min, and finally 800ml of deionized water is added and stirred evenly.

[0058] Comparative Example 1

[0059] The following is a preparation process of a lubricant, as follows:

[0060] 10g of graphene oxide raw material was first immersed in 60ml of organic solvent dimethylformamide, fully stirred, and then subjected to 800W microwave heating for 10min to strip oxygen in the graphene oxide. The obtained 1.2g of graphene was immediately added to the prepared 400ml poly-α-olefin base oil with added surface modifier, stirred evenly, and put into a microwave graphene preparation furnace, set the microwave parameter to 200W, heated to 40°C, and then 10ml of modified long-chain alkane dispersant (octadecane bromide), 10ml of halogenated hydrocarbon pour point depressant (n-butyl bromide), and 10ml of ethylene propylene copolymer viscosity index improver (ethylene propylene copolymer T613) were added in sequence, and microwave dispersion treatment was performed for 10min to integrate the above materials into the base oil; then 10ml of polycarboxylic acid corrosion inhibitor, 10ml of oleic acid octadecylamine rust inhibitor, and 10ml of dialkyl dithiocarbamate antioxidation additive were added, and microwave dispersion treatment was performed at 800W for 60min. Finally, 800ml of deionized water was added and stirred evenly.

[0061] Comparative Example 2

[0062] The following is a preparation process of a lubricant, as follows:

[0063] 1g of graphene oxide raw material was first immersed in 10ml of organic solvent dimethylformamide, fully stirred, and then subjected to 800W microwave heating for 10min to strip oxygen in the graphene oxide. The obtained 0.12g of graphene was immediately added to the prepared 100ml poly-α-olefin base oil with added surface modifier, stirred evenly, and put into a microwave graphene preparation furnace, set 200W microwave parameters, heated to 40°C, and then 10ml of modified long-chain alkane dispersant (octadecane bromide), 10ml of halogenated hydrocarbon pour point depressant (n-butyl bromide), and 10ml of ethylene propylene copolymer viscosity index improver (ethylene propylene copolymer T613) were added in sequence, and microwave dispersion treatment was performed for 10min to integrate the above materials into the base oil; then 10ml of polycarboxylic acid corrosion inhibitor, 10ml of oleic acid octadecylamine rust inhibitor, and 10ml of dialkyl dithiocarbamate antioxidation additive were added, and microwave dispersion treatment was performed at 800W for 60min. Finally, 1100ml of deionized water was added and stirred evenly.

[0064] Comparative Example 3

[0065] The following is a preparation process of a lubricant, as follows:

[0066] 1g of graphene oxide raw material was first immersed in 60ml of organic solvent dimethylformamide, fully stirred, and then subjected to 800W microwave heating for 10min to strip oxygen from the graphene oxide. The obtained 0.12g of graphene was immediately added to the prepared 400ml poly-α-olefin base oil with added surface modifier, stirred evenly, and put into a microwave graphene preparation furnace, set the microwave parameter to 200W, heated to 40°C, and then 50ml of modified long-chain alkane dispersant (octadecane bromide), 50ml of halogenated hydrocarbon pour point depressant (n-butyl bromide), and 50ml of ethylene propylene copolymer viscosity index improver (ethylene propylene copolymer T613) were added in sequence, and microwave dispersion treatment was performed for 50min to integrate the above materials into the base oil; then 50ml of polycarboxylic acid corrosion inhibitor, 50ml of oleic acid octadecylamine rust inhibitor, and 50ml of dialkyl dithiocarbamate antioxidation additive were added, and microwave dispersion treatment was performed at 800W for 60min. Finally, 600ml of deionized water was added and stirred evenly.

[0067] The lubrication performance of Example 1 and Comparative Examples 1, 2, and 3 was tested, and the results are shown in Table 1 below.

[0068] Method: GB / T 3142-1982 "Determination of load-bearing capacity of lubricants (four-ball method)".

[0069] Test item: Lubricant load-bearing capacity determination method. The results are shown in Table 1.

[0070] Table 1 Lubrication performance test

[0071]

[0072]

[0073] Among them, the additives in the above table include dispersants, pour point depressants, viscosity index improvers, corrosion inhibitors, rust prevention additives and antioxidant additives.

[0074] From the results in Table 1, it can be seen that the rust-proof performance of the present invention has excellent lubrication performance. In Comparative Examples 1 and 2, the graphene content is too high or the base oil content is too low, resulting in incomplete dispersion of the graphene in the base oil, and the performance of the resulting lubricant is reduced; in Comparative Example 3, the content of the additive is too high, which leads to a decrease in the content of graphene in the lubricant, affecting the lubrication effect of the lubricant.

[0075] The friction coefficient test was conducted on the lubricant obtained in Example 1 of the present invention. The test was conducted at room temperature of 25°C and the metal was selected to have an area of ​​10 cm 2 , 2mm thick 316L stainless steel sheet, after applying lubricant to the 316L stainless steel sheet and keeping it for 3 hours, it was cleaned by centrifugation with deionized water and ethanol. In the test experiment of the friction tester, the friction coefficient of the rust-proof lubricant of the present invention is about 0.043-0.046, and the friction coefficient of the medical device lubricant sold on the market is about 0.050-0.055. Compared with the medical device lubricant sold on the market, the lubrication effect of the present invention is improved by about 10%-20%.

[0076] The lubricant obtained in Example 1 of the present invention and the medical device lubricant sold on the market were used to test the anti-rust performance. The experiment was carried out at room temperature of 27°C. The metal selected in this test was an area of ​​10 cm 2 , 2mm thick 316L stainless steel sheets were also compared with common medical equipment lubricants sold on the market. 6% FeCl3 and 0.05mol / L HCl were used for pitting corrosion. The ferric chloride test method refers to a laboratory test method in which the material is immersed in a ferric chloride solution to induce pitting corrosion. It is used to test the pitting corrosion resistance of stainless steel and chromium-containing nickel-based alloys in oxidizing chloride media. It can also be used to study the effects of alloying elements, heat treatment and surface state on the corrosion resistance of the above alloys. Similar to the friction coefficient experiment, the 316L stainless steel sheet was tested after applying the lubricant for 3 hours and then centrifugally washed with deionized water and ethanol. The time when corrosion spots appeared on the 316L stainless steel sheet was observed and recorded. Pitting corrosion is slight corrosion or scattered local corrosion found on the surface of metal materials, and generally the pore diameter of pitting corrosion is less than 1mm, and the depth is less than the pore diameter. Such as Figure 1As shown in the figure, it was found that the corrosion spots appeared on the 316L stainless steel sheet coated with the anti-rust lubricant of the present invention in about 1 hour, while the 316L stainless steel sheet coated with the Ruhof medical device lubricant had obvious corrosion spots in about 50 minutes. Compared with the Ruhof medical device lubricant, the anti-rust performance of the lubricant of the present invention is improved by about 10%-20%. Figure 2 As shown, the comparative example 1 has corrosion spots in about 1 hour; Figure 3 As shown, the comparative example 2 has corrosion spots in about 1 hour; Figure 4 As shown, comparative example 3 also had corrosion spots in about 1 hour.

[0077] In the anti-rust performance test of the present invention, as above, the possible higher temperature of 50°C under the working state of the medical device load is selected, and the same test metal, pitting material and lubricant are selected. It is found that the time for corrosion points to appear on the 316L stainless steel sheet coated with the anti-rust lubricant of the present invention is still about 1h, while the 316L stainless steel sheet coated with the commercial medical device lubricant has obvious corrosion points in about 45min. Compared with the commercial medical device lubricant, the anti-rust performance is improved by about 15%-30%. Comparative Examples 1, 2, and 3 also have relatively good anti-pitting performance under large temperature differences. This shows that the protective film formed by the lubricant of the present invention can still exist relatively stably at a higher temperature, and compared with the commonly used medical lubricants on the market, the anti-rust lubricant of the present invention has better anti-rust performance.

[0078] Test item: Anti-rust performance test, the results are shown in Table 2.

[0079] Table 2 Antirust performance test

[0080] serial number Time for corrosion spots to appear (27℃) Time for corrosion spots to appear (50℃) Example 1 1h 1h Ruhof Medical Device Lubricants 50min 45min Comparative Example 1 1h 1h Comparative Example 2 1h 58min Comparative Example 3 1h 55min

[0081] Medical devices are usually sterilized after cleaning and lubrication. After lubrication, an oil film coating is left on the surface of the medical device. To determine whether the oil film is penetrated and does not affect the sterilization process, a sterilization penetration test is performed.

[0082] Method: T / WSJD002-2019 Hygiene Requirements for Medical Cleaning Agents.

[0083] Test items: Cleaning agent test results, see Table 3.

[0084] Table 3 Cleaning agent test results

[0085]

[0086]

[0087] As can be seen from Table 3, the anti-rust property of the present invention has excellent antibacterial properties. In Examples 2 and 3, the experiment used a nanocomposite material synthesized from zinc oxide nanoparticles with a particle size of about 12 nm and graphene. In a culture dish with an E. coli content of 0-240 μg / ml, adding a graphene composite material at a concentration of equal to or greater than 60 μg / ml can completely inhibit the growth of E. coli; and it also has a good inhibitory effect on Staphylococcus aureus and pathogenic E. coli. When the concentration of the composite material is 120 μg·mL -1 The inhibition rate can reach about 99%.

[0088] Since the graphene content in Comparative Examples 1, 2, and 3 is greater than or equal to 60 μg / ml, the growth of Escherichia coli has been completely inhibited, and a good inhibitory effect is also achieved on Staphylococcus aureus and pathogenic Escherichia coli.

[0089] Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A rust-proof lubricant, characterized in that: It includes the following components by weight: 10-60 parts of base oil; Graphene 0.001 to 1 part; Dispersant 0.1-3 parts; Pour point depressant 0.1 to 3 parts; 0.1 to 1 part of viscosity index improver; Corrosion inhibitor 0.1-3 parts; 0.1 to 1 part of anti-rust additive; Antioxidant additive 0.1-1 part; 27 to 89.4 parts of water.

2. The rust-proof lubricant according to claim 1, characterized in that: The base oil includes a poly-alpha-olefin base oil and / or a mineral oil.

3. A rust-proof lubricant according to claim 1 or 2, characterized in that: The graphene is prepared by heating a graphene precursor with microwaves; the graphene precursor includes at least one of graphite, graphite oxide, nanographene particles, graphene flakes, graphene composite materials, graphene derivative materials, and graphene oxide materials.

4. The rust-proof lubricant according to claim 1, characterized in that: The dispersant includes at least one of isopropanol, cerium dioxide nanoparticles, α-Fe2O3 nanorods, modified long-chain alkanes with 10 to 30 carbon atoms, stearic acid, oleic acid, and doped graphene; The pour point depressant comprises at least one of modified graphene, halogenated hydrocarbons, organic alcohols and poly-α-olefins, wherein the modified graphene comprises at least one of a long-chain alkyl group having 10 to 50 carbon atoms, a carboxyl group, a sulfonic acid group, an amino group and a fluoroalkyl group; The viscosity index improver comprises at least one of hydrogenated styrene diene copolymer, polymethacrylate, ethylene propylene copolymer and polyisobutylene; The corrosion inhibitor comprises an organic phosphonic acid and / or a polycarboxylic acid; The anti-rust additive includes at least one of octadecylamine oleate, cyclohexylamine stearate, and nitrogen heterocyclic compounds; the antioxidant additive includes at least one of antimony dialkyl dithiocarbamate, zinc dialkyl dithiocarbamate, dialkyl dithiocarbamate, butylated hydroxytoluene, and tert-butylhydroquinone.

5. The method for preparing a rust-proof lubricant according to claims 1 to 4, characterized in that: The graphene is mixed with the base oil, and then a dispersant, a pour point depressant and a viscosity index improver are added, and then a corrosion inhibitor, an anti-rust additive, an antioxidant additive and water are added to obtain the product.

6. The method for preparing a rust-proof lubricant according to claim 5, characterized in that: The base oil is preheated to 35-50°C.

7. The method for preparing a rust-proof lubricant according to claim 5, characterized in that: The preparation process of the graphene is as follows: a graphene precursor is dispersed in an organic solvent and then subjected to microwave heating to obtain the graphene.

8. The method for preparing a rust-proof lubricant according to claim 7, characterized in that: The organic solvent includes at least one of N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran and chloroform; The microwave heating conditions are: power of 600-800W, and time of 1-30min.

9. The method for preparing a rust-proof lubricant according to any one of claims 5 to 8, characterized in that: The whole process of preparing the anti-rust lubricant adopts microwave dispersion of materials or ultrasonic dispersion of materials.

10. The use of a rust-proof lubricant according to claims 1 to 4, characterized in that: As an anti-rust lubricant for medical devices.

Citation Information

Patent Citations

  • Graphene-containing lubricating oil and preparation method thereof

    CN106497654A

  • Graphene-synergized lubricating antirust oil and preparation method thereof

    CN107603706A

  • Preparation method of graphene-containing lubricant additives and / or lubricating grease additives

    CN107955671A

Cited By

  • Anti-wear composition, preparation method and lubricating oil containing anti-wear composition

    CN120865980A